Effects of adding sucrose on Penaeus monodon (Fabricius, 1798) growth performance and water quality in a biofloc system. (7th July 2016) - Huang, Jianhua; Yang, Qibin; Ma, Zhenhua; Zhou, Falin; Yang, Lishi; Deng, Jipeng; Jiang, Shigui
Abstract: A 60‐day indoor growth trial was conducted to study the effects of biofloc on the growth performance of a Penaeus monodon (Fabricius, 1798), water quality and biological indicators including biofloc volume, chlorophyll‐ a, heterotrophic bacteria and Bacillus quantity. Two concentrations of sucrose (0 and 75%) were added daily to the P. monodon culture systems (2.94 ± 0.11 g), which were conducted indoors in fibre‐glass tanks (500 L). Results showed that the final body weight and weight gain of the adding 75% sucrose group were significantly higher ( P  <   0.05) than that of the control, as well as significantly ( P  < 0.05) improved specific growth rates and survival rates, and reduced feed coefficient. Adding 75% sucrose promoted heterotrophic bacteria, Bacillus and phytoplankton reproduction, and significantly ( P  < 0.05) reduced the concentration of ammonia‐N (NH4 ‐N), nitrite‐N (NO2 ‐N) and nitrate‐N (NO3 ‐N). The changes of water quality indicators in the two groups showed the similar trend at the end of the experiment, and the ammonia‐N, nitrite‐N, nitrate‐N and phosphate‐P concentrations in the 75% sucrose group were significantly ( P  < 0.05) lower than those of the control group, Chlorophyll‐ a concentrations peaked at 389.12 μg/L in the biofloc sucrose group at 18:00 h, and heterotrophic bacteria peaked 8 h after sucrose was added. The addition of sucrose also reduced the pH of the water. Our research showed that adding sucrose promoted biofloc formation and shortened the formation time; increased the number of heterotrophic bacteria and algae which might play a role in improving water quality by assimilating ammonia‐N and other harmful substances in the water; supplemented food for P monodon growth; and reduced the feed coefficient.